2002
DOI: 10.1177/107906320201400203
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Risk Factors: The Kia Marama Evaluation

Abstract: Risk assessment is an essential part of clinical practice. Each of the three aspects of risk (static, stable, and acute dynamic) are important at various points of contact between the man and the systems that are responsible for providing service. Dynamic factors, the typical treatment and supervision targets, have received less research attention than static factors. This paper examined the extent to which pretreatment, posttreatment and change scores were associated with reoffending among men incarcerated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 33 publications
4
60
0
1
Order By: Relevance
“…In partial correlations, n = 289 for intrafamilial child molesters, n = 197 for extrafamilial child molesters, n = 81 for rapists, and n = 58 for mixed offenders. * p < .001. more accurately capture general violent tendencies versus those sexual in nature; however, consistent with previous literature, hostility was predictive of recidivism in this sample (Firestone et al, 1999(Firestone et al, , 2000Thornton, 2002;Ward et al, 2002) and complemented the RRASORmod in the prediction of recidivism. Given the predictive value of hostility beyond the RRASOR-mod, the present findings confirm and encourage treatment efforts directed toward the management of hostility and anger in sexual offenders.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In partial correlations, n = 289 for intrafamilial child molesters, n = 197 for extrafamilial child molesters, n = 81 for rapists, and n = 58 for mixed offenders. * p < .001. more accurately capture general violent tendencies versus those sexual in nature; however, consistent with previous literature, hostility was predictive of recidivism in this sample (Firestone et al, 1999(Firestone et al, , 2000Thornton, 2002;Ward et al, 2002) and complemented the RRASORmod in the prediction of recidivism. Given the predictive value of hostility beyond the RRASOR-mod, the present findings confirm and encourage treatment efforts directed toward the management of hostility and anger in sexual offenders.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, hostility was the best predictor of recidivism compared to the other self-report psychometric measures examined (r = .18 for sexual recidivism; r = .22 for violent [including sexual] recidivism). Other researchers found that rumination of anger was related to sexual recidivism in groups of mixed child molesters (Hudson, Wales, Bakker, & Ward, 2002;Thornton, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Given the potential for bias that might be present in clinicians' reports, future research adopting a rating approach similar to the one used here could base ratings of progress/gains on offenders' homework (e.g., offence cycle and relapse prevention plan assignments) or perhaps on videotaped material from treatment sessions. The use of other measures, particularly self-report measures with established psychometric properties (see Hudson, Wales, Bakker, & Ward, 2002), represent an alternative, or complimentary, approach that would negate the difficulties associated with low interrater reliability that can arise when rating file material. Given that self-report measures are also subject to problems (e.g., response bias), the use of multiple measures of the relevant constructs might be a desirable, though resource intensive, approach to ensure both reliability and validity.…”
Section: Discussionmentioning
confidence: 98%
“…There is a certain consensus suggesting that the most important dynamic risk factors can be classified into six categories (Beech, Fisher & Thornton, 2003;Hanson & Harris, 2001;Beech, 1998;Thornton, 2002): (a) sexual self-regulation and sexual interests which encompass various manifestations such as a high sexual drive, being overwhelmed by sexual thoughts and urges, and deviant sexual interests; (b) distorted beliefs and attitudes regarding sex offending and/or victims which taps into the lack or limited internal constraints against offending; (c) socio-affective deficits which refers among other things to difficulties developing healthy, respectful, and intimate relationships; (d) self-regulation deficits or difficulties to plan ahead, solve problems, and control negative emotions; (e) noncooperation with community supervision, such as being disengaged and manipulative, and; (f) the presence of a social network, if any, that is composed mainly of negative social influences as opposed to positive prosocial influences. These criminogenic needs can be contrasted with non-criminogenic needs, needs that have not been shown to be related to a new conviction for a sex crime, such as the offender's emotional functioning (e.g., depression, anxiety) and interpersonal competence (e.g., self-esteem, loneliness, social avoidance) (e.g., Hudson, Wales, Bakker, & Ward, 2002). Past research has shown that dynamic risk factors are as important as static, historical factors (e.g., Gendreau et al, 1996).…”
Section: Dynamic Factors and Community Risk Managementmentioning
confidence: 99%